2011
DOI: 10.1016/j.jtbi.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model for durotaxis

Abstract: Cell migration is a phenomenon that is involved in several physiological processes. In the absence of external guiding factors it shares analogies with Brownian motion. The presence of biochemical or biophysical cues, on the other hand, can influence cell migration transforming it in a biased random movement. Recent studies have shown that different cell types are able to recognise the mechanical properties of the substratum over which they move and that these properties direct the motion through a process cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
0
26
2
Order By: Relevance
“…We find that soft-to-stiff durotaxis is a necessary consequence of stiffness-dependent persistence, with or without a rigidity-dependent crawling speed. The mechanism we uncover is fundamentally different from those reported in earlier theoretical works on durotaxis [20,21]: the cells take no directional cues from the gradient re- Simulated trajectories (2D model) of 50 cells, departing from the origin at t = 0 with a linear velocity of 50 µm/hr on a persistence gradient, increasing linearly from 0.2 to 2 hrs over the x-range [−0.1, 0.1] mm (i.e., ∆τp/∆x = 9 hrs/mm). The cells were tracked for 12 hrs, their positions recorded at 6-minute intervals.…”
contrasting
confidence: 99%
“…We find that soft-to-stiff durotaxis is a necessary consequence of stiffness-dependent persistence, with or without a rigidity-dependent crawling speed. The mechanism we uncover is fundamentally different from those reported in earlier theoretical works on durotaxis [20,21]: the cells take no directional cues from the gradient re- Simulated trajectories (2D model) of 50 cells, departing from the origin at t = 0 with a linear velocity of 50 µm/hr on a persistence gradient, increasing linearly from 0.2 to 2 hrs over the x-range [−0.1, 0.1] mm (i.e., ∆τp/∆x = 9 hrs/mm). The cells were tracked for 12 hrs, their positions recorded at 6-minute intervals.…”
contrasting
confidence: 99%
“…In both cases, it has been observed that mesenchymal cells migrate preferentially toward the regions of higher stiffness. Several models have been proposed to explain and describe durotaxis [16,17,18]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the general case the cell migration can be also affected by external forces F , which can cause for instance chemotaxis [1], durotaxis [2,3], etc. In this case the existing gradient of the surface properties forces the cells to migrate along to.…”
mentioning
confidence: 99%